ANALISIS KEJADIAN INFEKSI SALURAN KEMIH BERDASARKAN PENYEBAB PADA PASIEN DI POLIKLINIK UROLOGI RSUD DR. M. YUNUS BENGKULU - liza fitri lina; Dwi Puji Lestari (JURNAL KEPERAWATAN MUHAMMADIYAH BENGKULU, 2019)
Â Urinary infection is a pathological condition that has been known for a long time and can be found in various primary health services to subspecialty. The purpose of this study was to analyze the incidence of infection urinary tract in patients at the urological clinic poly Dr. M Yunus Bengkulu. The research design used qualitative with a descriptive approach. The informant's research method in this study used the "Purposive Sampling" technique. The source of information in this study was patients who visited the urology clinic poly Dr. Married M Yunus Bengkulu and data from the medical clinic of the urology clinic Dr. RSUD M Yunus Bengkulu as many as 5 patients. Data collection uses in-depth interview techniques. The results of this study obtained a theme namely, a etiological aspect. In the etiological aspect, it is found the patient have a habit of holding urine and drinking less water, especially at certain times and circumstances. The conclusions were the informants understood a little about urinary infections, all informants had experienced urinary tract infections for the first time, the sexual activities carried out by informants were reasonable or mediocre sexual activity, all informants had the habit of sometimes holding back urination, especially in when certain activities such as long trips and work, and all informants have the habit of drinking water.Â Keywords: Infection, Knowledge, Etiology, Handling.